BUSINESS PERFORMANCE OF AGGREGATOR BUSINESS IN AGRICULTURE DURING COVID-19 PANDEMIC - Janita Sembiring Meliala; Siti Jahroh (Journal of Islamic, Social, Economics and Development, 2022)
Advances in information technology (IT) have also driven a change from traditional approaches to new approaches in agriculture or in other words the revolution in the fourth agricultural sector (Agriculture 4.0). IT has triggered the emergence of aggregator business in agriculture. With the Covid-19 outbreak, movement restrictions were made so that the majority of buying and selling was carried out online. The existence of restricted movement due to the Covid-19 pandemic has decreased farmers' income due to difficulties in selling their products, while consumers who usually shop at the market switched to online shopping. The intermediary, in this case the aggregator that connects farmers directly with consumers online, will be of great help to both parties. Thus, this study aims to (1) analyze the business processes of the aggregator business during Covid-19 and (2) analyze the business performance of the aggregator business during Covid-19 compared to before. The questionnaire survey through google form was distributed to aggregator business players in September 2020. The data were analyzed by descriptive statistics through tabulation. Based on our findings, there are two important points. Firstly, through the advance of information technology, the aggregators were able to connect the agribusiness system, i.e., farmers in on-farm, inputs supplier in up-stream, distributors in the down-stream, as well as government in the supporting sub-systems, in order to deliver agricultural products to the customers. TH is the agricultural business aggregator that connects the whole agribusiness system. Secondly, based on the business performance, Covid-19 pandemic has affected agricultural business aggregators differently due to its business nature. It seems that vegetables, fruits and staple foods as the essential goods for a living contributed to the higher business performance of agricultural business aggregators.